Association of Serum C- Reactive protein (CRP) With Migraine (Bangladesh Journal of Neuroscience, 2026)
Background: Migraine is a highly prevalent and frequently disabling neurovascular disorder. The aim of the present study was to compare the serum level of CRP between migraine patients and others headache patient without migraine to see whether CRP isabnormally increased in patients with migraine.Methods: This comparative crosssectional study was conducted at the department of Neurology, Mymensingh Medical College & Hospital. Total 150 patients with headache were selected according to selection criteria following informed written consent. They were divided into two groups, one group included patients who had headache with migraine and another group who had headache without migraine. Detailed clinical examination, proper history taking was done and serum level of CRP was measured of all patients. After collection of all the required data, final analysis was carried out by using the SPSS 23.0.Results: Among 150 patients, mean age of patients with migraine was 31.08 ± 11.29 years and without migraine was 31.37 ±11.53 years. Both groups were similar in terms of demographic profile (p>0.05). Serum CRP levels were significantly higher in patients with migraine than the patients without migraine (12.36±7.34 Vs 7.54±4.28, p